Na+,K+-ATPase is the membrane receptor of hormone ouabain - Isabel Larre; Marcelino Cereijido (Communicative & Integrative Biology, 2010)
At 10 nM, ouabain elicits changes in cell contacts, which are independent and usually in opposite direction to effects occurring at μM levels, suggesting that these depend on entirely different mechanisms.1 However, this does not discard the possibility that in both instances ouabain would act on the same receptor. We demonstrate that such is the case by comparing the response of wild and ouabain-resistant MDCK cells on a very special type of cell contact, the tight junction (TJ).